Photoresponsive Surface Molecularly Imprinted Polymers for the Detection of Profenofos in Tomato and Mangosteen - Chen, Mei-jun; Yang, Hai-lin; Si, Ya-min; Tang, Qian; Chow, Cheuk-fai; Gong, Cheng-bin (Frontiers in Chemistry, 2020)
As a moderately toxic organophosphorus pesticide, profenofos is widely used in agricultural practice, resulting in the accumulation of high-concentration profenfos in agricultural products and environment. This will inevitably damage our health. Therefore, it is important to establish a convenient and sensitive method for the detection of profenofos. This paper reports a photoresponsive surface imprinted polymers (PS-co-PMAA@PSMIPs) for the detection of profenofos by using carboxyl-capped polystyrene microspheres (PS-co-PMAA), profenofos, 4-((4-(methacryloyloxy) phenyl)diazenyl) benzoic acid, and triethanolamine trimethacrylate as the substrate, template, functional monomer, and cross-linker, respectively. The PS-co-PMAA@PSMIPs shows good photoresponsive properties in DMSO/H2O (3:1, v/v). Its photoisomerization rate constant exhibits a good linear relationship with profenofos concentration in the range of 0 ~ 15 μmol/L. The PS-co-PMAA@PSMIPs was applied for the determination of profenofos in spiked tomato and mangosteen with good recoveries ranged in 94.4%-102.4%.